1978
DOI: 10.1073/pnas.75.6.2603
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5,8-oxyretinoic acid isolated from small intestine of vitamin A-deficient rats dosed with retinoic acid.

Abstract: A retinoid was isolated by a multistep procedure from the small intestines of vitamin A-deficient rats given a single dose of retinoic acid. The compound, designated 8II, was pure, as demonstrated by four high-pressure liquid chromatographic procedures. It was positively identified as 5,8-oxyretinoic acid by ultraviolet spectrophotometry, mass spectrometry, and spectral and chromatographic comparison to known compounds. It is probable that 5,8-oxyretinoic acid was produced from 5,6-epoxyretinoic acid under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…As earlier attempts to identify the products of CYP26A have lacked physico-chemical approaches, the application of LC-MS and tandem MS conditions to detect and characterize these highly labile retinoids has provided an additional level of confidence to the identification work. While many of the hydroxylations we ascribe to CYP26A have been previously reported in various biological systems (7)(8)(9)(10)(11)(12)(13)(14), this is the first demonstration that all such metabolites can be produced by CYP26A alone. Furthermore, the gene dose and time course experiments indicate that atRA can be repeatedly hydroxylated to produce a series of increasingly water-soluble products, thereby giving credence to the theory that CYP26A is a catabolic system for protecting the cell from further stimulation by a potently biologically active signaling molecule.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As earlier attempts to identify the products of CYP26A have lacked physico-chemical approaches, the application of LC-MS and tandem MS conditions to detect and characterize these highly labile retinoids has provided an additional level of confidence to the identification work. While many of the hydroxylations we ascribe to CYP26A have been previously reported in various biological systems (7)(8)(9)(10)(11)(12)(13)(14), this is the first demonstration that all such metabolites can be produced by CYP26A alone. Furthermore, the gene dose and time course experiments indicate that atRA can be repeatedly hydroxylated to produce a series of increasingly water-soluble products, thereby giving credence to the theory that CYP26A is a catabolic system for protecting the cell from further stimulation by a potently biologically active signaling molecule.…”
Section: Discussionmentioning
confidence: 94%
“…The emergence of a family of inducible retinoic acid-metabolizing cytochrome P450 proteins (P450-RAIs or CYP26s) with high specificity for atRA across species simply reinforces the importance of maintaining a tight regulation of the levels of this highly potent ligand inside all cells (2)(3)(4)(5)(6). Over the past two decades, several catabolic steps have been suggested for reducing the biological activity of atRA, including: a ) oxidation at the 4 position of the ␤ -ionone ring (7)(8)(9); b ) oxidation at C-18 (9, 10); c ) 5,6-epoxidation (11)(12)(13)(14); and d ) glucuronidation (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Two of these metabolites were identical with synthetic all- trans -4-hydroxy-RA and all- trans -4-oxo-RA (Frolik et al 1978; McCormick et al 1978a; Frolik et al 1979). Napoli and colleagues identified 5,8-oxy-RA as a metabolite of administered all- trans -RA in the intestine of vitamin A deficient rats (Napoli et al 1978). However, it was pointed out that the in vivo product was most likely the 5,6-epoxide of RA and that 5,8-oxy-RA was derived from 5,6-epoxide under the acidic conditions of the extraction procedure (McCormick et al 1978b; Napoli et al 1978).…”
Section: 2 Historymentioning
confidence: 99%
“…The remaining two pathways apparently involved oxidative loss of the C-14 and C-15 positions. Further studies, after the advance of techniques in retinoid analysis, reported the identification of metabolites formed in vivo, in cells, or in cell-free membrane systems (17, 24, 25, 30, 31, 57, 58, 63, 84–86). From these early studies, the principal oxidative reaction in RA metabolism was postulated to be catalyzed by an enzyme or enzymes with properties similar to cytochrome P450–mediated monooxgenase systems, based on the localization of activity to the microsomal fraction, the requirement for oxygen and nicotinamide adenine dinucleotide phosphate (NADPH) for catalysis, and the inhibition of RA metabolism by carbon monoxide (84, 85).…”
Section: Introductionmentioning
confidence: 99%